2021
DOI: 10.1051/e3sconf/202131207018
|View full text |Cite
|
Sign up to set email alerts
|

On the use of tapered channels gas distributors to promote convection in PEM Fuel Cells

Abstract: Polymeric Exchange Membrane Fuel Cells (PEMFC) are promising power propulsion systems for the decarbonization of the transportation sector. Despite being a well-known method for the direct production of electric current from the reactants chemical energy, one of the major limitations to their large-scale industrial development are fluid dynamics and mass transport aspects, crucially limiting the electrochemistry rate under critical conditions. This is especially verified in PEMFC with serpentine-type gas distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In this paper, the optimization methods of the current flow channel structure of PEMFC are summarized. For the research on bipolar plates, D ' Adamo and Borghi (2021) conducted a multidimensional CFD study on the traditional and conical channel distributors through numerical analysis of the limited area of the serpentine gas distributor and the scale-less analysis, The combined effects of pressure loss, catalyst layer utilization, a flow state of anisotropic diffusion medium and convective/diffusion equilibrium were evaluated. Based on the simulation results, it was concluded that channel coning is a very effective method to improve the power density of PEMFC [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, the optimization methods of the current flow channel structure of PEMFC are summarized. For the research on bipolar plates, D ' Adamo and Borghi (2021) conducted a multidimensional CFD study on the traditional and conical channel distributors through numerical analysis of the limited area of the serpentine gas distributor and the scale-less analysis, The combined effects of pressure loss, catalyst layer utilization, a flow state of anisotropic diffusion medium and convective/diffusion equilibrium were evaluated. Based on the simulation results, it was concluded that channel coning is a very effective method to improve the power density of PEMFC [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…For the research on bipolar plates, D ' Adamo and Borghi (2021) conducted a multidimensional CFD study on the traditional and conical channel distributors through numerical analysis of the limited area of the serpentine gas distributor and the scale-less analysis, The combined effects of pressure loss, catalyst layer utilization, a flow state of anisotropic diffusion medium and convective/diffusion equilibrium were evaluated. Based on the simulation results, it was concluded that channel coning is a very effective method to improve the power density of PEMFC [1,2]. Abraham B and Murugavel K, (2021) conducted a numerical simulation of proton exchange membrane fuel cells by using the computational fluid dynamics (CFD) model in ANSYS FLUENT software.…”
Section: Introductionmentioning
confidence: 99%